Pembiasaan Berdoa Dapat Mengubah Perilaku Anak Usia 4-5 Tahun di RA Al-Kautsar Cilamaya Karawang - Hasanah, Nurul (Jurnal CARE (Children Advisory Research and Education), 2023)
THE HABIT OF PRAYING CAN CHANGE THE BEHAVIOR OF CHILDERN AGED 4-5 YEARS IN RA AL-KAUTSAR CILAMAYA. This reseach aims to informations about the habit of praying in children aged 4-5 years at RA Al-Kautsar Cilamaya. Find out how the behavior of praying in children, theacher strategies, and evaluations carried out by teachers. This research was conducted in a descriptive qualitative from with data collection techniques in the from of interviews, observations, and documentation. The subjects in this study were children aged 4-5 years who were members of group A which collected 18 children. The result of this study indicate that habituation of praying behavior smoothly and optimally, children show good behavior in praying activities although it seems that there are still children who have not shown good behavior. The role of class teachers and accompanying teachers is very active in guiding and directing children to get used to good behavior when praying.